Financing the Next Silicon Valley - Darian M. Ibrahim (Washington University Law Review, 2010)
Silicon Valley's success has led other regions to attempt their own high-tech transformations, yet most imitators have failed. Entrepreneurs may be in short supply in these “non-tech” regions, but some non-tech regions are home to high-quality entrepreneurs who relocate to Silicon Valley due to a lack of local financing for their start-ups. Non-tech regions must provide local finance to prevent entrepreneurial relocation and reap spillover benefits for their communities. This Article compares three possible sources of entrepreneurial finance—private venture capital, state-sponsored venture capital, and angel investor groups—and finds that angel groups have distinct advantages when it comes to funding innovation in non-tech regions. This entrepreneurial finance story is then supplemented by a “law and entrepreneurship” story—specifically, a look at securities laws that might impede optimal levels of angel group financing.
Keywords: Entrepreneurship; Venture capital; Capital investments